Passiflora quimiana, a new species from the Cordillera del Cóndor: Ecuador's far‐flung frontier - Kuethe, J. R.; Garzón‐Suárez, Henry; Jiménez, Marco M.; Zavatin, Danilo A.; Goucher, Dave Randall (Nordic journal of botany, 2025)
A new species of Passiflora subgenus Decaloba, supersect. Decaloba, from the Cordillera del Cóndor in Ecuador, is described and illustrated, with its morphological similarities to other species being discussed in this paper. Passiflora quimiana exhibits the unique combination of narrow ovate to long‐oval leaves and small foliaceous bracts. Morphologically it is the most similar to Passiflora quadriflora from Peru, from which it differs by the size of the floral organs, the foliaceous bracts, the structure of the corona, with the inner series slightly swollen at the apices, and the raised limen. It is currently known from a single locality only, occurring as a vine in submontane vegetation of sandstone plateaus.